Editorial (diségno, 2019)
The editorial team of Diségno opens the n. 4 of the journal with a dedication to Vito Cardone who left us prematurely on 17 April. To him we owe the birth of Diségno and to him we, all the editorial team, owe the formulation of the magazine described in the editorial of n. 1. Vito Cardone was a unique scholar, an engineer with a passion for reading and he knew how to combine this peculiarity with a rigorous method and great dynamism. His enthusiasm has infected all of us and not only because of the novelty of the project, but also because we were convinced of  the need to equip a scientific society with a journal that was not a mere “institutional bulletin”, but rather a place of exchange and scientific comparison on the founding themes of our discipline and on the less explored and unusual areas of research. (read more)